DESIGN OF INT ERNAL CONTROL SYSTEM, ACCOUNTING RECORDS, AND FINANCIAL REPORTING IN JUNE’S MARKET - Sukiantono Tang; Fiorentina Fiorentina (ConCEPt - Conference on Community Engagement Project, 2022)
This activity was done to apply accounting knowledge learned during the university study to daily business practice. Besides, this activity also aims to help micro-business entrepreneurs make accounting records and financial reports accurately and correctly to reflect the business economy situation. The object of this activity is June’s Market, a micro-business that operates online and still uses manual records on books, also not having a good financial report. These conditions were known by visiting the business place and also by interviewing. This activity results in an accounting system designed in Microsoft Access program so that entrepreneurs can easily do the records and the system can automatically create financial reports. This system can also improve business flow to a more efficient and effective business operation.